Performance Optimization of Bhabinkamtibmas through Binluh to Prevent Crime of Fraud in the Jurisdiction of Demak Police - Nadhira Bella Shafira (Advances in Police Science Research Journal, 2022)
Criminal frauds that is still rife in Demak Regency, has an impact on changes in the condition of Kamtibmas in the jurisdiction of the Demak Police.The presence of this fraud crime is certainly one of the duties of the police, especially in Bhabinkamtibmas, which has an important role in handling and leading the public to always be vigilant against fraud. Knowing the optimization of the performance of Bhabinkamtibmas members and analyzing the optimization of the guidance of counseling by Bhabinkamtibmas itself, the author uses the concept of bhabinkamtibmas, and the concept of optimization. The theoretical studies that the author uses are management theory, and performance theory. In this study, the author uses a qualitative approach. The data source used is the primary data source and the secondary data source. The data collection techniques used in this study are interviews, observations, and document studies. The findings of research conducted by the authors show that there are still some things that are not optimal in the performance of Bhabinkamtibmas and counseling guidance activities carried out. This is because some members of Bhabinkamtibmas have not implemented Dikjur, and the counseling material provided has not been on target, so cases of fraud still occur. The advice of the author in the research from the results of this paper is the need for vocational training for Bhabinkamtibmas members regularly, as well as the implementation of Binluh selectively prioritizes so that the Kamtibmas message is conveyed properly to prevent fraud that occurs in the jurisdiction of the Demak Police.